Combining moral commitment with pragmatism : Ashok Mitra Commission on Education - Amrik Singh
Three things stand out about the report of the Education Commission appointed by the West Bengal Government under the Chairmanship of Ashok Mitra.First, except for professional education, the entire educational scene is surveyed and hardly anything worth while has been ignored or left out. Second, the report is not only an analysis of the problems, it is also "a feasible programme of educational goals and objectives for the short run as well as the longer time frame". Finally, while it informed by a certain measure of moral commitment, what the report has to say is utterly free of dogma; it is nothing if not pragmatic.
Keywords: Education and State -- India -- West Bengal; Boards and Commissions -- India -- West Bengal